2018
DOI: 10.1002/hep4.1176
|View full text |Cite
|
Sign up to set email alerts
|

Baseline urine metabolic phenotype in patients with severe alcoholic hepatitis and its association with outcome

Abstract: Severe alcoholic hepatitis (SAH) has a high mortality rate, and corticosteroid therapy is effective in 60% patients. This study aimed to investigate a baseline metabolic phenotype that could help stratify patients not likely to respond to steroid therapy and to have an unfavorable outcome. Baseline urine metabolome was studied in patients with SAH using ultra‐high performance liquid chromatography and high‐resolution mass spectrometry. Patients were categorized as responders (Rs, n = 52) and nonresponders (NRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In addition, we have previously shown that steroid nonresponse could be due to failure of cellular energy metabolism. High levels of acetyl carnitine in SAH are associated with high mortality . It is possible that G‐CSF therapy could help in restoring cellular energy and hepatic regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have previously shown that steroid nonresponse could be due to failure of cellular energy metabolism. High levels of acetyl carnitine in SAH are associated with high mortality . It is possible that G‐CSF therapy could help in restoring cellular energy and hepatic regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of acetyl carnitine in SAH are associated with high mortality. (21) It is possible that G-CSF therapy could help in restoring cellular energy and hepatic regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Acetyl-Lcarnitine levels of >2,500 ng/mL reliably segregated survivors from non-survivors (P< 0.01, log-rank test) in the study cohort. 3 This low cost test, if validated in other studies, could be of help in selection of patients for steroid therapy.…”
Section: Metabolic Markers For Early Detection Of Steroid Responsementioning
confidence: 97%
“…Whether baseline metabolic phenotype could identify non-re-sponders and those with unfavorable outcome was investigated. 3 Baseline urine metabolome of SAH patients was subjected to ultra-high performance liquid chromatography and high-resolution mass spectrometry. Nine urinary metabolites linked to mitochondrial functions significantly discriminated non-responders, most importantly the increased acetyl-L-carnitine (12-fold) levels.…”
Section: Metabolic Markers For Early Detection Of Steroid Responsementioning
confidence: 99%
See 1 more Smart Citation